THE EXISTENCE OF THE APPLICATION OF CRIMINAL COVER-UP TO INDONESIAN CRIMINAL LAW IN THE PERSPECTIVE OF THE PRINCIPLE OF EQUALITY BEFORE THE LAW - Zulkifli (Proceeding International Conference on Social Sciences, 2026)
The application of the principle of equality before the law in criminal law enforcement has not been carried out as the spirit outlined by the Criminal Code which upholds Human Rights by setting aside all forms of differences and backgrounds that exist in defendants of any criminal act. the existence of the application of criminal cover-up in the Indonesian criminal law system and its analysis from the perspective of the Principle of Equality Before the Law. Cover crime, which is regulated in Law Number 20 of 1946, is a type of crime that provides an exemption from ordinary prison sentences, especially for convicts with a certain position or status background, with the aim of maintaining their honor and dignity. This paper examines the policy of determining criminal cover from a criminal perspective, especially from the purpose of punishment. Based on the purpose of punishment formulated in the Criminal Code Bill, the purpose of punishment will not be achieved by using criminal means of cover-up. Cover crime also has the potential to cause discrimination because there is no measure for judges to impose these criminal sanctions. To provide legal certainty, lawmakers should clearly formulate criteria for judges to impose criminal sanctions for cover-up. This study shows that the crime of cover-up is still positively recognized in the Indonesian criminal law system even though the frequency of its application is very rare and can only be imposed by the High Court. However, its existence causes a contradiction with the essence of the Principle of Equality Before the Law guaranteed by the Constitution. This principle demands that every citizen should be treated equally regardless of background, position, or social status. The granting of preferential treatment—i.e. placement in an institution separate from ordinary prisoners and without the obligation of forced labor—for certain groups through criminal cover-up has the potential to violate the principle of universal equality. Therefore, despite having a formal legal basis, the criminal cover is seen as irrelevant to the spirit of criminal law reform that upholds substantive justice and equality in the modern era. It is recommended that the criminal cover be reviewed and considered for removal from the Criminal Code (KUHP) or criminal legislation in the future in order to strengthen the full implementation of the Principle of Equality Before the Law in Indonesia.